1984
DOI: 10.1177/00220345840630050201
|View full text |Cite
|
Sign up to set email alerts
|

The Volume of Saliva in the Mouth Before and After Swallowing

Abstract: In 20 male and 20 female adult subjects, the volume of saliva in the mouth before (VMAX) and after (RESID) swallowing was determined. RESID could be computed by measuring the potassium and chloride concentrations in unstimulated saliva and in the expectorate after a five-second rinse with 5 ml of water immediately following a swallow. The mean value of RESID after a normal swallow was significantly higher in males (0.87 ml) than in females (0.66 ml). After a forced swallow, RESID was only slightly but signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(123 citation statements)
references
References 8 publications
7
115
0
1
Order By: Relevance
“…30,31 It has been suggested that the anatomy and physiology of the mouth, including interproximal spaces, occlusion and soft tissue anatomy may influence the retention or clearance or liquids in the mouth. [32][33][34] The multifactorial analysis completed by Al-Malik et al 28 also found a significant association between erosion and frequency of fizzy drink consumption, with an odds ratio of 1.46, but this was for 2-5-year-olds. The demonstration of increased risk is not the same as the identification of aetiology and attempts to show a causal relationship between risk factors and erosion have failed, although the sample sizes were small.…”
Section: Main Studymentioning
confidence: 99%
“…30,31 It has been suggested that the anatomy and physiology of the mouth, including interproximal spaces, occlusion and soft tissue anatomy may influence the retention or clearance or liquids in the mouth. [32][33][34] The multifactorial analysis completed by Al-Malik et al 28 also found a significant association between erosion and frequency of fizzy drink consumption, with an odds ratio of 1.46, but this was for 2-5-year-olds. The demonstration of increased risk is not the same as the identification of aetiology and attempts to show a causal relationship between risk factors and erosion have failed, although the sample sizes were small.…”
Section: Main Studymentioning
confidence: 99%
“…During the recordings, subjects sat quietly with the head tilted slightly downwards so that any saliva in the mouth would drain forward. The subjects were told not to swallow (Lagerlof & Dawes, 1984) or to speak unless absolutely necessary. Nose breathing was encouraged to minimize drying of the oral mucosa (Cannon, 1918;Jenkins, 1978 Five healthy male volunteers took part in this experiment.…”
Section: Introductionmentioning
confidence: 99%
“…16,18 One of the functions of saliva is to regulate the pH of the oral environment by salivary buffers. 19 According to as a result, they obtained 1 ml/min saliva secreted under stimulation and 0.37 ml/min without stimulation. From a conservative perspective, taking into account the value of 1ml/min, the results presented in Table 2 and the data Graph 1: Representative of the pH behavior of a sample from each group, depending on the volume of saliva added proposed by Lagerlöf and Dawes 19 (1984), according to whom, when taking liquids, the remaining average volume in the oral cavity will be 1 ml, one can estimate that it will take 5 to 7 minutes, on average, to raise the pH level above 5.5 after taking cola-based drinks.…”
Section: Discussionmentioning
confidence: 97%